Pseudomodes of Schrödinger operators - Krejčiřík, David; Siegl, Petr (Frontiers in Physics, 2024)
Pseudomodes of non-self-adjoint Schroedinger operators corresponding to large pseudoeigenvalues are constructed. The approach is non-semiclassical and extendable to other types of models including the damped wave equation and Dirac operators.